Exploring the role of insulin resistance in bridging the metabolic syndrome and Alzheimer’s disease-a review of mechanistic studies - Wang, Shilei; Shi, Yuqing; Xin, Rui; Kang, Hailan; Xiong, Huazhong; Ren, Jixiang (Frontiers in Endocrinology, 2025)
The association between metabolic syndrome (MetS) and Alzheimer’s disease (AD) has attracted widespread attention; nevertheless, the precise mechanism of action between the two is not yet fully elucidated. This review systematically explores the complex mechanisms of insulin resistance (IR) in MetS and AD. We first detail the intrinsic mechanisms of insulin resistance and emphasize its central role in the pathophysiology of MetS. Further, we reveal the underlying mechanisms by which insulin resistance in turn triggers AD through a multidimensional pathway that promotes the accumulation of pathological products, induces blood-brain barrier dysfunction, impairs neuroplasticity, induces neuroinflammatory responses, aberrantly activates the renin-angiotensin-aldosterone system, and exacerbates oxidative stress. In addition, we summarize potential strategies for targeting IR in AD treatment and demonstrate the promising prospects for improving insulin resistance in promoting cognitive recovery. This study offers a novel theoretical framework for elucidating the intricate relationship between MetS and AD. Furthermore, it provides a scientific foundation for the formulation of preventive and therapeutic strategies for metabolic and neurodegenerative diseases.